N. F. S. Grundtvig og naturalismen - Nyborg, Ole (Grundtvig-Studier, 2012)
N. F. S. Grundtvig og naturalismen [N. F. S. Grundtvig and the Concept of Naturalism] By Ole Nyborg The concepts o f ‘naturalism’, ‘naturalist’, and ‘naturalistic’ are frequently found in the writings of the Danish theologian N. F. S. Grundtvig (1783-1872), and this is the case during his whole lifetime. In scholarly literature, Grundtvig’s concept of ‘naturalism’ has mainly been interpreted from the way ‘naturalism’ etc. is used in his introduction to Nordisk Mythologi (Northern Mythology) (1832). The frequent references to ‘naturalism’ in Grundtvig’s other works have mostly been neglected by scholars. However, an analysis of Grundtvig’s works as a whole shows a very clear picture. He is a persistent, emotional, and aggressive opponent to naturalism, emphasizing numerous negative aspects of it as a philosophy, because its modern individualistic ideas destroy the natural bonds and social constraints of love, reverence, and respect. According to Grundtvig, naturalism represents a powerful, imminent, and dangerous threat to traditional Christian states and nations of Western Europe, and the notorious revolution of France of 1789 he sees as a terrible and horrifying manifestation of the unchristian, subversive, unbridled, and immoral character of naturalism.